Kuat Tekan Dan Kuat Tarik Belah Sebagai Nilai Estimasi Kekuatan Sisa Pada Beton Serat Kasa Aluminiumakibat Variasi Suhu - Wariyatno, Nanang Gunawan; Haryanto, Yanuar (Dinamika Rekayasa, 2013)
This study was aimed to determine influence of temperature variation to the compressive strength and split cylinder strength of aluminium wire-mesh fibre concrete. Specimen was concrete cylinder with 15 cm in diameter and 30 cm in high, and the volume fraction of aluminium wire-mesh fibre was specified equal to 0.2%. Temperature variations applied in this research were 25oC (room temperature), 400oC and 800oC. The result showed that increasing of temperature had caused compressive strength reduction.Compressive strength at temperature 400oC and 800oC for both normal concrete and wire-mesh fibre concrete were equal to 22.04%, 39.21%, 21.68% and 45.81%. Split cylinder test at temperature 400oC and 800oC for both normal concrete and wire-mesh fibre concrete showed reduction which were equal to 20.36%, 51.27%, 21.98% and 56.30%. On the other hand modulus of elasticity reduction at temperature 400oC and 800oC for both normal concrete and wire-mesh fibre concrete were 2.20%, 65.22%, 6.79% and 61.33%, where all of tests werecompared to normal concrete and wire-mesh fibre concrete at room temperature (25oC).